Prevalence of Multi-Drug Resistant Tuberculosis in the Dominican Republic: A Systematic Literature Review, 2024 - Islam, Dr Monirul; Weaver, Chaston; Cruz, Dr Modesto (International Journal of Innovative Research in Medical Science, 2024)
Objective: This systematic review assessed available published data related to the prevalence of multidrug-resistant tuberculosis (MDR-TB) in the Dominican Republic (DR). The prevalence of MDR-TB in the DR is among the highest in the Americas. To better understand the barriers associated with increasing rates of MDR-TB, a focused effort must be made in the identification of the actual rates of MDR-TB present in the DR. As of 2024, there remains much variability in the limited amount of published data regarding the actual rates of MDR-TB in the DR. Methods: A database search was conducted in Medline via PubMed, Cochrane Library, CINAHL Plus Full Text via EBSCOhost, and Web of Science for manuscripts published through January 2024 using keywords “Multi-Drug-Resistant Tuberculosis” in combination with “Dominican Republic.” In addition, Google Scholar was referenced to capture “grey literature.” Studies published in English estimating the rate of MDR-TB or extensively resistant TB rates were included. The study protocol was registered at PROSPERO (CRD42024529219). Risk of bias was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool for prevalence studies. Results: Sixteen published papers were eligible for full article review. Four of these met the selection criteria for the final analysis. The reported MDR-TB rates ranged from 5% to 15% for new cases and 30% to 44% for previously treated TB cases. Conclusions: The wide variations in the prevalence of MDR-TB may be related to varying methods used for rate calculations. Our findings show limited data from the DR on national MDR-TB rates.